Regulation of the Intranuclear Distribution of the Cockayne Syndrome Proteins. Issue 1 (December 2018) - Iyama, Teruaki; Okur, Mustafa; Golato, Tyler; McNeill, Daniel; Lu, Huiming; Hamilton, Royce; Raja, Aishwarya; Bohr, Vilhelm; Wilson, David
Abstract Cockayne syndrome (CS) is an inherited disorder that involves photosensitivity, developmental defects, progressive degeneration and characteristics of premature aging. Evidence indicates primarily nuclear roles for the major CS proteins, CSA and CSB, specifically in DNA repair and RNA transcription. We reveal herein a complex regulation of CSB targeting that involves three major consensus signals: NLS1 (aa467-481), which directs nuclear and nucleolar localization in cooperation with NoLS1 (aa302-341), and NLS2 (aa1038-1055), which seemingly optimizes nuclear enrichment. CSB localization to the nucleolus was also found to be important for full UVC resistance. CSA, which does not contain any obvious targeting sequences, was adversely affected (i.e. presumably destabilized) by any form of truncation. No inter-coordination between the subnuclear localization of CSA and CSB was observed, implying that this aspect does not underlie the clinical features of CS. The E3 ubiquitin ligase binding partner of CSA, DDB1, played an important role in CSA stability (as well as DDB2), and facilitated CSA association with chromatin following UV irradiation; yet did not affect CSB chromatin binding. We also observed that initial recruitment of CSB to DNA interstrand crosslinks is similar in the nucleoplasm and nucleolus, although final accumulation is greater in the former. Whereas assembly of CSB at sites of DNA damage in the nucleolus was not affected by RNA polymerase I inhibition, stable retention at these sites of presumed repair was abrogated. Our studies reveal a multi-faceted regulation of the intranuclear dynamics of CSA and CSB that plays a role in mediating their cellular functions.